Hubungan Beban Kerja Perawat dengan Ketepatan Triage Pasien di IGD Rumah Sakit - Utami, Dia Rejeki; Fitriani.K, Fitriani.K; Wotok, Nobertus Wuli (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Triage is a crucial process in emergency services that determines the priority of patient care based on their severity. Triage accuracy is significantly influenced by various factors, one of which is nurse workload. A high workload can lead to decreased focus and accuracy in triage assessments. Objective: To determine the relationship between nurse workload and patient triage accuracy in the Emergency Department (ED) of a hospital. Methods: This study used a quantitative analytical design with a cross-sectional approach. The population was all ED nurses at Hospital X, with a sample of 35 people drawn using total sampling. The instruments used were a workload questionnaire (NASA-TLX) and a triage accuracy observation sheet based on the Emergency Severity Index (ESI) standard. Data were analyzed using the Spearman test. Results: Most nurses (68.6%) had a high workload. Triage accuracy was classified as accurate in 60% of nurses. The Spearman test results showed a significant relationship between workload and triage accuracy (p = 0.003; r = -0.489). Conclusion: There is a significant and meaningful relationship between nurse workload and patient triage accuracy. High workload is associated with decreased accuracy in determining triage categories. Recommendation: Hospital management is expected to pay attention to nurse-to-workload ratios and provide regular triage training.